Meloidogyne Species Associated with Weeds in Rio Grande do Sul - BELLÉ,C. (2019)
ABSTRACT: The frequency of species of root-knot nematodes (Meloidogyne spp.) was evaluated in weeds collected in different fallow farms in the State of Rio Grande do Sul, Brazil. In the samples where the nematode was found, the species of the root-knot nematode was identified by electrophoresis using the isozyme esterase. They were obtained from weeds belonging to 24 weed species from 13 different botanical families: Amaranthaceae, Asteraceae, Commelinaceae, Convovulaceae, Cyperaceae, Euphorbiaceae, Lamiaceae, Malvaceae, Oxalidaceae, Poaceae, Portulacaceae, Solanaceae, Verbenaceae. Meloidogyne javanica Est J3 (Rm: 1.0, 1.25, 1.40) was the most frequent species and occurred in 53.3% of the samples. M. arenaria with phenotype Est. A2 (Rm: 1.20, 1.30) was detected in 15.6% of the samples. M. incognita Est. I2 (Rm: 1.0, 1.1), M. ethiopica Est. E3 (Rm: 0.9, 1.15, 1.30), M. enterolobii Est. M2 (Rm: 0.7, 0.75, 0.9, 0.95) and M. hapla Est. H1 (Rm: 1.17) in 13.3%, 8.9%, 6.7% and 2.2% of the samples, respectively. Therefore, knowledge of the range of host plants to different species of the root-knot nematode can positively contribute to the adoption of management practices that allow the reduction of their populations in the soil.